2010
DOI: 10.1177/0886260510390956
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to Participating in Dating Violence Research: Are Our Questions Distressing Participants?

Abstract: In recent years, there has been increased research focus on dating violence, producing important information for reducing these violent relationships. Yet Institutional Review Boards (IRBs) are often hesitant to approve research on dating violence, citing emotional distress of participants as a possible risk of participation. However, no known research has examined the reactions of research participants to questions about dating violence. The current study examined the reactions among college students to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
60
4
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 24 publications
12
60
4
2
Order By: Relevance
“…We also modified the response options (ranging from "never since we broke up" to "more than 20 times since we broke up"), so that they would be consistent with the response options on the Conflict Tactics Scale-Revised (CTS2; Straus, Hamby, Boney-McCoy, & Sugarman, 1996), which was used to screen for Physical (12 items; for example, "pushed or shoved me"), Sexual (five items; for example, "made me have sex without a condom"), and Psychological (four items; for example, "called me fat or ugly") partner abuse in conjunction with the harassment subscale of the CAS at the initial study session. Of note, we only used the severe items of the psychological abuse subscale of the CTS2, as identified by Straus et al (1996), given that the moderate psychological abuse items (e.g., "yelled at me") are extremely common in dating relationships and may reflect normative arguing rather than psychological abuse (Edwards et al, 2011;Shorey, Cornelius, & Bell, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…We also modified the response options (ranging from "never since we broke up" to "more than 20 times since we broke up"), so that they would be consistent with the response options on the Conflict Tactics Scale-Revised (CTS2; Straus, Hamby, Boney-McCoy, & Sugarman, 1996), which was used to screen for Physical (12 items; for example, "pushed or shoved me"), Sexual (five items; for example, "made me have sex without a condom"), and Psychological (four items; for example, "called me fat or ugly") partner abuse in conjunction with the harassment subscale of the CAS at the initial study session. Of note, we only used the severe items of the psychological abuse subscale of the CTS2, as identified by Straus et al (1996), given that the moderate psychological abuse items (e.g., "yelled at me") are extremely common in dating relationships and may reflect normative arguing rather than psychological abuse (Edwards et al, 2011;Shorey, Cornelius, & Bell, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Given these concerns, over the past decade or so researchers have begun to assess participants' reactions to participation in interpersonal violence research. This research suggests that only a small number (i.e., 4% to 5%) of participants report experiencing negative emotional reactions in the immediate aftermath of participating in this type of research and that these negative reactions are correlated with participants' more generalized levels of psychological distress (Carlson et al, 2003;DePrince & Freyd, 2004;Edwards, Kearns, Calhoun, & Gidycz, 2009;Shorey, Cornelius, & Bell, 2011). However, previous studies have failed to simultaneously and comprehensively assess participants' reactions to survey questions that inquire about multiple forms (i.e., sexual, physical, psychological) of interpersonal violence in different developmental periods (i.e., childhood, adolescence, adulthood).…”
Section: Abstract Interpersonal Violence Victimization Ethics Resementioning
confidence: 95%
“…Research has also demonstrated that social desirability may impact reports of dating violence (Bell and Naugle 2007;Shorey et al 2011b), and it is also possible this impacts disclosure of stalking behaviors. Future research should examine how social desirability impacts findings.…”
Section: Limitationsmentioning
confidence: 99%